2009
DOI: 10.1111/j.1558-5646.2009.00931.x
|View full text |Cite
|
Sign up to set email alerts
|

The Dual Benefits of Aposematism: Predator Avoidance and Enhanced Resource Collection

Abstract: Theories of aposematism often focus on the idea that warning displays evolve because they work as effective signals to predators.Here, we argue that aposematism may instead evolve because, by enhancing protection, it enables animals to become more exposed and thereby gain resource-gathering benefits, for example, through a wider foraging niche. Frequency-dependent barriers (caused by enhanced conspicuousness relative to other prey and low levels of predator education) are generally assumed to make the evolutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
60
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(63 citation statements)
references
References 55 publications
2
60
0
1
Order By: Relevance
“…In the pairwise analyses (Table S2), we found significant correlations (P < 0.01) between aposematism, diet specialization, body mass, and two measures of aerobic capacity (AMR and scope). These results suggest that the appearance of a phylogenetic correlation between aposematism and aerobic capacity preceded enhanced resource gathering, which in turn promoted diet specialization (8). An alternative explanation is that diet specialization preceded the origin of higher aerobic capacity, assuming prey are a patchy resource (30), with aposematism evolving as a defense against predators.…”
Section: Phylogenetic Analysis Of Aposematism Diet Specialization Bodymentioning
confidence: 84%
See 2 more Smart Citations
“…In the pairwise analyses (Table S2), we found significant correlations (P < 0.01) between aposematism, diet specialization, body mass, and two measures of aerobic capacity (AMR and scope). These results suggest that the appearance of a phylogenetic correlation between aposematism and aerobic capacity preceded enhanced resource gathering, which in turn promoted diet specialization (8). An alternative explanation is that diet specialization preceded the origin of higher aerobic capacity, assuming prey are a patchy resource (30), with aposematism evolving as a defense against predators.…”
Section: Phylogenetic Analysis Of Aposematism Diet Specialization Bodymentioning
confidence: 84%
“…Two alternative hypotheses characterize the sequence of adaptations leading to the integration of aposematism and scale in poison frogs. First, as a preexisting predator deterrent, aposematism allowed individuals to increase resource-gathering abilities in the form of high aerobic capacity and diet specialization (8). Under this alternative, aposematism initially linked chemical defense with a generalist diet; however, this diet must have included some alkaloidbearing arthropods.…”
Section: Phylogenetic Analysis Of Aposematism Diet Specialization Bodymentioning
confidence: 99%
See 1 more Smart Citation
“…These opportunity costs are not generally considered to apply to aposematism. Speed et al [56] make the important point that greater freedom to exploit resources may be an important selective pressure encouraging evolution of aposematism. We would also argue that aposematism might influence other aspects of life-history through this mechanism.…”
Section: Integrating Warning Signals More Generally Into Behavioural mentioning
confidence: 99%
“…This became known as the "escape-and-radiate" hypothesis (2). Similarly, it has been suggested that bright coloration can reduce the constraints of hiding, enabling niche expansion and promoting diversification in animal prey (3,4). The escape-and-radiate hypothesis is influential in the adaptive radiation literature (2,5,6) but has been tested surprisingly rarely (6)(7)(8).…”
mentioning
confidence: 99%